Cytochrome P450 VvCYP76F14 dominates the production of wine bouquet precursors in wine grapes - Xia, Guangli; Shi, Matthew; Xu, Weina; Dark, Adeeba; Song, Zhizhong (Frontiers in Plant Science, 2024)
In wine grape, the multi-functional cytochrome P450 enzyme VvCYP76F14 sequentially catalyzes the formation of linalool-derived compounds, including (E)-8-hydroxylinalool, (E)-8-oxolinalool, and (E)-8-carboxylinalool, which are crucial precursors for the wine bouquet. However, molecular basis towards VvCYP76F14 in regulating the wine bouquet precursor production remain unknown. In this study, both wine bouquet precursor contents and catalytic activities of VvCYP76F14s varied among the three different wine bouquet type varieties. Subcellular localization analysis revealed that VvCYP76F14s are predominantly localized in the endoplasmic reticulum. Notably, a maltose-binding protein (MBP) fusiontag was added to each of the three VvCYP76F14 proteins in the Escherichia coli expression system, significantly induced the concentration of the MBP-VvCYP76F14 fusion proteins. Site-directed mutation of 4 amino acid residues (I120L, L298V, E378G, and T389A) in VvCYP76F14 resulted in a significant decrease in VvCYP76F14 enzymatic activities, respectively. Furthermore, the transient expression of VvCYP76F14 cloned from 'Yanniang No.2' significantly increased the levels of (E)-8hydroxylinalool, 8-oxolinalool, and (E)-8-carboxylinalool compounds in the transformed 'Yanniang No.2', 'Italian Riesling', and 'Marselan' berries, respectively. In conclusion, VvCYP76F14 dominates the production of wine bouquet precursors and could be a fingerprint marker for screening superior hybrid offspring with desired levels of wine bouquet precursors.